Analysis of The Effect International Prices, Exchange Rates, Non-Tarif Measures, and Import Volume On The Export Value Of Indonesian Cloves (Hs:0907) To India - Krisna Adi Jonathan; Renny Oktafia (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of international prices, the rupiah–rupee exchange rate, non-tariff measures, and India’s import volume on the export value of Indonesian cloves to India. The research utilizes secondary data for the period 2015–2024. The analytical method employed is the Autoregressive Distributed Lag (ARDL) model to examine both short-run and long-run relationships, complemented by stationarity tests, cointegration tests, ECM estimation, and diagnostic and stability tests. The results show that international prices have a positive and significant effect on Indonesia’s clove export value, consistent with export-supply theory which states that higher global prices increase export incentives. The rupiah–rupee exchange rate displays a positive but insignificant relationship, indicating that exchange rate volatility is not sufficiently strong to influence changes in export value. Non-tariff measures, including SPS and TBT standards, are found to have a significant effect, reflecting the role of regulations in increasing compliance costs while simultaneously enhancing Indian consumer confidence in the quality of Indonesian cloves. India’s import volume also has a significant influence, showing that India’s domestic demand remains a major driver of Indonesia’s export value during the study period. This study is expected to provide insights for policymakers and industry players in strengthening trade strategies, particularly in enhancing the competitiveness of Indonesian clove exports through quality improvements, exchange rate stability, and compliance with non-tariff standards.